Fuel consumption of a sugarcane harvester in different operational settings - Ramos, Carlos R. G. [UNESP]; Lancas, Kleber P. [UNESP]; Lyra, Gabriel A. de; Sandi, Jefferson [UNESP] (Univ Federal Campina Grande, 2016)
The interventions performed during the mechanized harvesting are essential to improve the operational performance of sugarcane harvesters and reduce operational costs. The objective of the present study was to evaluate the fuel consumption of a sugarcane harvester in different forward speeds and engine rotations. Harvesting was conducted in a green cane plot, with the variety RB 855156. Flow meters were installed in the harvester's fuel supply system and an electronic device was used for data acquisition. The experiment was carried out in a completely randomized design in a factorial scheme (3 x 2), using three engine rotations and two forward speeds, with six replicates. Harvesting capacity and fuel consumption per hour, per area and per ton of harvested sugarcane were analyzed. The results were subjected to analysis of variance and means were compared by Tukey test. The variations in engine rotation did not affect the performance for harvesting capacity, but influenced fuel consumption. Forward speed influenced both harvesting capacity and fuel consumption.
Keywords: mechanized harvesting; operational performance; harvesting capacity